Meiotic Heterogeneity of Trivalent Structure and Interchromosomal Effect in Blastocysts With Robertsonian Translocations - Zhang, Shuo; Lei, Caixia; Wu, Junping; Zhou, Jing; Xiao, Min; Zhu, Saijuan; Xi, Yanping; Fu, Jing; Sun, Yijuan; Xu, Congjian; Sun, Xiaoxi (Frontiers in Genetics, 2021)
Background: Robertsonian translocations are the common structural rearrangements and have an increased genetic reproductive risk due to the existence of trivalent structure during meiosis. Studies found trivalent structure shows obviously meiotic heterogeneity between different translocation carriers, while the factors causing heterogeneity have not been well elaborated till now and whether interchromosomal effect (ICE) phenomenon occurs in comparison with suitable non-translocation control patients has not yet been reported. Herein, we aim to evaluate the factors that cause meiotic heterogeneity of trivalent structure and the ICE phenomenon. Methods: We designed a retrospective study, totally 217 Robertsonian translocation carriers and 134 patients with the risk of transmitting monogenic inherited disorders (RTMIDs) that underwent preimplantation genetic testing (PGT) were collected between March 2014 and December 2019. The segregation products of trivalent structure were analyzed according to the carrier’s gender, age and translocation type. In addition, aneuploidy abnormalities of non-translocation chromosomes from Robertsonian carriers were compared with those of the genome from patients with RTMIDs to analyze ICE phenomenon. Results: We found the percentage of alternate segregation pattern in male carriers was significantly higher (P<0.001, OR=2.95) than that in female carriers, whereas the frequency of adjacent segregation pattern was lower (P<0.001, OR=0.33). By contrast, no difference was observed between young and older carriers when performing stratified analysis by age. In addition, segregation pattern was associated with the D;G chromosomes involved in Robertsonian translocation, the rate of alternate segregation pattern in Rob(13;14) carriers was significantly higher (P=0.010, OR=1.74) than that in Rob(14;21) carriers, whereas the frequency of adjacent segregation pattern was lower (P=0.032, OR=0.63). Moreover, the results showed the trivalent structure could significantly increase the frequencies of chromosome aneuploidies 1.30 times in Robertsonian translocation carriers compared with patients with RTMIDs (P=0.026), especially for the male and young subgroups (P=0.030, OR=1.35 and P=0.012, OR=1.40), while the mosaic aneuploidy abnormalities presented no statistical difference. Conclusions: Our study demonstrates meiotic segregation heterogeneity of trivalent structure is caused by the carrier’s sex and translocation type, and it is independent of carrier’s age. ICE phenomenon exists during meiosis and then affects the genome stability, increasing the frequencies of additional chromosome abnormalities.